2021
DOI: 10.1007/978-3-030-72699-7_17
|View full text |Cite
|
Sign up to set email alerts
|

Automated, Explainable Rule Extraction from MAP-Elites Archives

Abstract: Quality-diversity (QD) algorithms that return a large archive of elite solutions to a problem provide insights into how high-performing solutions are distributed throughout a feature-space defined by a user -they are often described as illuminating the feature-space, providing a qualitative illustration of relationships between features and objective quality. However, if there are 1000s of solutions in an archive, extracting a succinct set of rules that capture these relationships in a quantitative manner (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In previous work [27,28,29] we have demonstrated that MAP-Elites can be used provide a diverse set of optimised solutions in a combinatorial optimisation setting, specifically capacitated vehicle routing. While there have been significant developments to the MAP-Elites algorithm since its first introduction, the vast majority have been evaluated in the context of robotics and generative design [15,11,6], using continuous representations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work [27,28,29] we have demonstrated that MAP-Elites can be used provide a diverse set of optimised solutions in a combinatorial optimisation setting, specifically capacitated vehicle routing. While there have been significant developments to the MAP-Elites algorithm since its first introduction, the vast majority have been evaluated in the context of robotics and generative design [15,11,6], using continuous representations.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been significant developments to the MAP-Elites algorithm since its first introduction, the vast majority have been evaluated in the context of robotics and generative design [15,11,6], using continuous representations. Little attention has been paid to translating these to a combinatorial optimisation setting where there is significant potential for using the family of MAP-Elites algorithms to provide users with increased choice [26,27,29]. We proposed two methods for increasing the solutions returned (s) and diversity (qd) in a combinatorial setting of MAP-Elites: the first used multiple decodings of the same genome, while the second used a range of emitters with a multi-arm bandit to dynamically choose operators to generate new solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work [27,28,29] we have demonstrated that MAP-Elites can be used provide a diverse set of optimised solutions in a combinatorial optimisation setting, specifically capacitated vehicle routing. While there have been significant developments to the MAP-Elites algorithm since its first introduction, the vast majority have been evaluated in the context of robotics and generative design [15,11,6], using continuous representations.…”
Section: Discussionmentioning
confidence: 99%
“…While there have been significant developments to the MAP-Elites algorithm since its first introduction, the vast majority have been evaluated in the context of robotics and generative design [15,11,6], using continuous representations. Little attention has been paid to translating these to a combinatorial optimisation setting where there is significant potential for using the family of MAP-Elites algorithms to provide users with increased choice [26,27,29]. We proposed two methods for increasing the solutions returned (s) and diversity (qd) in a combinatorial setting of MAP-Elites: the first used multiple decodings of the same genome, while the second used a range of emitters with a multi-arm bandit to dynamically choose operators to generate new solutions.…”
Section: Discussionmentioning
confidence: 99%